Superioritas Laki-Laki dalam Dunia Sufi: Tinjauan Budaya Islam dalam Praktek Kepemimpinan Spiritual - Abdur Rohmat (UIN Maulana Malik Ibrahim Malang, 2010)
Substantially, the spiritual teaching of Sufism is not represented and represents one of gender group, male or female an sich. The Sufism spiritual teaching has great universal scope for male and female. In the empirical domain, in fact, the spiritual teaching still conduct patrimonial culture behavior which makes the original Sufism spiritual teaching endangered to fail. This situation also happened in the leadership on the practices of tasawuf teaching culture which has been dominated by the males. As a consequence, the female will never get the chance to lead the teaching practice. The situation encourages the writer to dig up the issues on imbalance in the male and female role in the Sufism teaching practices. The article raises the questions on should the spiritual teacher be the male? And why does the leadership capacity of the spiritual teaching has been dominated by the male? Furthermore, the exploration will be helpful resource to have better understanding on the Sufism teaching practice. Secara substansial, ajaran spiritual tasawuf tidak terwakili dan mewakili salah satu kelompok gender, pria atau wanita saja. Ajaran spiritual Sufisme memiliki cakupan universal yang besar untuk pria dan wanita. Dalam ranah empiris sebenarnya ajaran spiritual masih melakukan perilaku budaya patrimonial yang membuat ajaran spiritual Sufisme asli terancam punah. Keadaan ini juga terjadi pada kepemimpinan pada praktik budaya pengajaran tasawuf yang telah didominasi oleh laki-laki. Sebagai konsekuensinya, perempuan tidak akan pernah mendapatkan kesempatan untuk memimpin praktik mengajar. Situasi tersebut mendorong penulis untuk menggali isu ketidakseimbangan peran pria dan wanita dalam praktik pengajaran tasawuf. Artikel tersebut mengangkat pertanyaan tentang apakah guru spiritual itu adalah laki-laki? Dan mengapa kapasitas kepemimpinan ajaran spiritual didominasi oleh laki-laki? Selanjutnya, eksplorasi akan menjadi sumber yang berguna untuk memiliki pemahaman yang lebih baik mengenai praktik pengajaran tasawuf.